Penerapan Arsitektur Eklektik Dalam Perancangan Waterfront Cottage Di Pantai Pasir Putih Papua Barat - Kinasih, Alifia Sekar Wana; Rahayu, Irma; Hildayanti, Andi (TIMPALAJA : Architecture Student Journals, 2023)
The Pasir Putih beach tourist attraction in West Papua is a recreational and religious attraction full of historical value, making it a mainstay for tourists visiting West Papua. This tourist attraction offers the natural beauty of its beaches, which are unique in their sea water which has three colors). However, the management aspects of Pasir Putih Beach are still not managed professionally by the government, and there is a lack of awareness among the local community. This design aims to support the existence of the Pasir Putih Beach tourist attraction. As a condition for developing the attractiveness of the tourist attraction, it is necessary to develop facilities that can accommodate every activity for the local community and tourists at the attraction. The design principle of Eclectic Architecture is to combine the styles and elements of traditional Papuan architecture and Scandinavian architecture in building design. The process goes through stages of data analysis and synthesis methods to produce a design for accommodation in the form of a cottage with several supporting facilities such as parks/green open spaces, recreation areas, children's play areas, and beach volleyball sports areas. It is hoped that this design can become a facility that can meet accommodation needs at the Pasir Putih Beach tourist attraction while also increasing its attraction for tourists by using a design that displays the beauty of the past and present in the shape of the building, ornaments, materials and coloring techniques so that it becomes its characteristic, which is different from other tourist attractions.